Synthesis, Spectroscopic and Biological Activities of Aromatic Schiff Base - Alam, Manawwer; M. Alandis, Naser; Rafi Shaik, Mohammed; Khan, Shahanavaj; Y. Alomar, Suliman (Asian Journal of Chemistry, 2014)
In this paper the preparation of 5-[(2-aminophenyl)imino]-3,3-dimethylcyclohexanone and 5-[(4-aminophenyl)imino]-3,3-dimethyl cyclohexanone in the ethanolic medium. The structures of these compounds were characterized by elemental analysis, FT-IR, 1H-NMR and 13C-NMR. The antibacterial and antifungal activity of these compounds has been investigated by agar disc diffusion method using Gram-negative and Gram-positive bacterial strain and four kinds of fungi.